Figurative Interpretation of Sound in the Heroic Epic Poetry of Peoples of Siberia - Kuzmina, Evgeniya N.; Arbachakova, Evgeniya N. Kuzmina, Lyubov N. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2022)
The authors of the article analyse the specifics of the depiction of sound and music in the heroic epic poetry of peoples of Siberia, who have preserved their epic tradition until recently. The authors refer to a number of epic texts by Altaians, Buryats, Tuvinians, Khakassians, and Shors. As demonstrated by the review of theoretical works carried out in the article, the musical aspect of the epic, which has attracted the attention of scholars, was focused on the study of epic intonation, timbre, and the use of musical instruments to accompany the storytelling (V. I. Verbitsky, V. V. Radlov, N. P. Dyrenkova, A. V. Anokhin, N. A. Baskakov, L. P. Potapov, Yu. I. Sheikin, R. B. Nazarenko, G. B. Sychenko, O. E. Dobzhanskaya, etc.). The use of the typological method makes it possible to carry out a comparative analysis of text fragments from the epics of the Turco-Mongol peoples, based on which it is concluded that noise sounds are conveyed in texts using onomatopoeias and ideophones. Music is conveyed through the description of its impact on characters, animals, and natural objects. It can be healing and destructive. These descriptions contain a sound code, which, like all other techniques of the epic, is aimed at conveying epic images. The oral nature of the functioning of folklore works makes it possible to use expressive techniques and means that give life to a certain monotony in the performance of monumental epic texts. More particularly, these include various ideophones. Descriptions of sounds, singing, and music are presented in stable poetic stereotypes in heroic epic poetry, which constitute the fund of the “common places” of the epic. The comparison of these descriptions shows their similarity in the structural, poetic, and compositional form, as well as in the same set of artistic and pictorial means used to create images.